Pengaruh Pemberian Minyak Atsiri Daun Bandotan (Ageratum conyzoides) Dalam Transportasi Tertutup Benih Ikan Koi (Cyprinus Carpio) [The Effects Of Bandotan Leave's (Ageratum conyzoides) Essential Oil within Closed System Transportation of Koi Carp (Cyprinus carpio) ] - Laksmi Sulmartiwi; Ida Bagus Putu Oka Dantika; Rr. Juni Triastuti (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract In the ornamental fish business, transportation has an important role to distributing fish up into the costumers. The distance between the farm and the customers location, require a transportation method which can maintain the quality and quantity of ornamental fish during the transportation. The biggest challenge in live fish closed system transportation is to reduce the stress level of fish during the process. According to Harmon (2009), fish are often exposed to multiple stressor during the transportation. Stressed fish can be seen through the increasing of tachiventilation (rapid opercula movement) and blood glucose levels (Evans and Claiborne, 2006). One of the method to reduce stress of fish during transportation is using essential oils from Bandotan's (A. conyzoides) leaves. A. conyzoides essential oils know has an analgesic activity (Okunade, 2002; Shekhar and Anju, 2012; Singh et al., 2013). A chemical compound with known analgesic effect, used in human and veterinary medicine as local analgesic dan be used to fish for the purpose of sedation, immobilization, and analgesia as well as general anaesthesia (Zahl and Samuelsen, 2012). This research was conducted to see the effect of A.conyzoides essential oils toward the survival rate, blood glucose levels, and tachyventilation of koi carp juveniles during closed system transportation. This research using completely randomized design method which consist of 5 different treatments with 4 replications. Treatment that used in this research is the variation of administration doses of A. conyzoides essential oils during the koi carp juvenile closed system transportation. The treatment such as A (5 ppm), B (10 ppm), C (15 ppm), D (20 ppm), and E (0 ppm). Main parameter of this research is survival rate, blood glucose levels, and tachyventilation of koi carp juvenile during 8 hours transportation. The result shows that A. conyzoides essential oils give a significant result toward survival rate, blood glucose levels, and tachiventilation of koi carp juvenile during transportation. There is no mortality in treatment A, B, and E, during transportation. The lowest blood glucose levels and tachiventilation found in treatment A (5 ppm).